Periodische und episodische Solifluktion im Rahmen der klimatischen Solifluktionstypen - Büdel, Julius (ERDKUNDE, 1959)
To begin with a more precise definition of the term solifluction is given. Then the phenomenology of this denudation process in the frost-split debris zone and the tundra of the present high arctic region (example: observations in South-Eastern Spitsbergen during the author’s expedition in 1959) is compared with the soliflual denudation phenomena in the analogous zones of the pleistocene cold periods then extending far into the middle latitudes (example: Central Europe). It is pointed out that the soliflual processes here as well as there show very characteristic differences despite of many a principal similarity. The differences are analyzed in detail and explained climatically. First of all the cold climates of the present high arctic region and of the pleistocene middle latitudes that control directly the soliflual processes show very pronounced differences in radiation. Secondly the respective climatic state of each of these zones was preceded by different climates in the past (climato-genetic evolution), which had created already different morphological and pedological initial conditions for the development of solifluction. It is further demonstrated that during cold periods (especially of the Wurm) in Central Europe a specific type of episodic solifluction, not yet surveyed systematically, came into existence on smooth slopes (angle of inclination varying between 1.7 to 4° respectively 6°; figs. 2-6). This type differs essentially and characteristically from the normal type of periodic solifluction (fig. 1). The latter type created soliflual mantles on steeper slopes, which predominate among the extended fossil traces in Central Europe and in the recent high arctic region. The type of episodic solifluction, however, came only into existence under the special conditions of the late pleistocene cold periods in the middle latitudes. Finally a diagram (fig. 7) gives a graphic synopsis of all the erosion processes, which were active in Central Europe during the Wurm under various conditions of inclination and rock resistance.